Transgressive Maternities: political-affective resignifications of women activists in the Chilean post-dictatorship - Gallardo Aranguren, Rocío; Guerra Pinto, Karina (Critical Proposals in Social Work, 2021)
There are certain memory practices within the post-dictatorship context in Chile associating women’s activism in antidictatorship struggles with the motherhood imaginary that, from an androcentric logic, reduce understanding of their political resistance by relating it to a male figure. However, these understanding are strained with other subaltern memories that, from a feminist analysis, allow to reconsider motherhood, sitting it in complex and dynamic sociopolitical contexts and highlighting its possibilities of agencies. Taking up the findings of a research on gender, memory and activism, the following article aims to analyze political and affective resignifications of women’s agencies that refer to motherhood and who mobilized against dictatorial violence, challenging the patriarchal structure. From this perspective, we hold the relevance of observing memory practices on women’s activism that allows us to make the understanding of historically subalternized political agencies more complex.